Barriers to providing internet-based home care services for urban older adults in China: a qualitative study of the service providers - Caiyun Qi; Yuan Wang; Xiaonan Qi; Yunhe Jiao; Chuanqi Que; Yufei Chen (BMC Geriatrics, 2023)
Abstract Background Due to the increasingly aging population in China and the changes in social and family structure, older adults’ care problems are becoming more and more prominent. To meet the home care needs of urban older adults, the Chinese government has launched Internet-Based Home Care Services (IBHCS). Although this model innovation can significantly relieve care problems, more and more evidence shows that there are many barriers in the process of IBHCS supply. The current literature is mostly from the perspective of the service users, and there are very few studies on the experience of service providers. Methods In this study, we took a qualitative phenomenological approach and used semi-structured interviews to investigate service providers’ daily experiences and the barriers they encounter. A total of 34 staff from 14 Home Care Service Centers (HCSCs) were included. Interviews were transcribed and analyzed using thematic analysis. Results We identified the barriers that service providers encounter in IBHCS supply: (1) bureaucratic repression: unreasonable policy plans, harsh assessment, excessive paperwork, different preferences of government leaders, and obstacles caused by COVID-19 control lead to a shift of focus in their work; (2) profitability crisis in the market: high service costs, dampened effective demand, government intervention in setting prices, and parent companies’ excessively high sales targets hinder the service supply process; (3) client-related challenges: the crisis of confidence, the dilemma of popularizing new technology, and communication barriers lead to rejection by older adults; (4) job dissatisfaction: low and unstable salary, heavy tasks, poor social acceptance of occupations, and lack of professional value reduce work enthusiasm. Conclusion We have investigated the barriers faced by service providers when providing IBHCS for urban older adults in China, providing empirical evidence in the Chinese context for the relevant literature. In order to provide IBHCS better, it is necessary to improve the institutional environment and market environment, strengthen publicity and communication, target customer needs, and adjust the working conditions of front-line workers.